Associations of urinary phthalate and phenol biomarkers with menarche in a multiethnic cohort of young girls - Wolff, Mary S. (Reprod Toxicol, 2016)
To study potential environmental influences on puberty in girls, we investigated urinary biomarkers in relation to age at menarche. Phenols and phthalates were measured at baseline (6–8 years of age). Menarche was ascertained over 11 years for 1051 girls with menarche and biomarkers. Hazards ratios were estimated from Cox models adjusted for race/ethnicity and caregiver education (aHR, 95% confidence intervals [CI] for 5th vs 1st quintile urinary biomarker concentrations). 2,5-Dichlorophenol was associated with earlier menarche (aHR 1.34 [1.06–1.71]); enterolactone was associated with later menarche (aHR 0.82 [0.66–1.03]), as was mono-3-carboxypropyl phthalate (MCPP) (aHR 0.73 [0.59–0.91]); the three p-trends were <0.05. Menarche differed by 4–7 months across this range. Enterolactone and MCPP associations were stronger in girls with below-median body mass index. These analytes were also associated with age at breast development in this cohort. Findings from this prospective study suggest that some childhood exposures are associated with pubertal timing.